2022
DOI: 10.3390/ijerph192416642
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among U-17, U-20, and Professional Female Soccer in the GPS Profiles during Brazilian Championships

Abstract: The purpose of this study was to compare and characterize the physical demand of official matches among under-17 (U-17), under-20 (U-20), and professional (Pro) female soccer players. All matches were from the U-17, U-20, and Pro National Brazilian Championships. Fourteen Pro matches, nine U-20 matches, and four U-17 matches were analyzed. The external load was measured by the global positioning system (GPS) and the internal workload was assessed by the ratings of perceived exertion (RPE) multiplied by the dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Female players covered a total distance of 9556 ± 795 m and 103 ± 6 m × min −1 during matches [ 30 41 , 43 , 45 , 48 63 , 65 70 ]. Considering zones of intensity, women soccer players performed 1429 ± 702 m in MSR, 830 ± 1414 m in HSR and 267 ± 275 m in sprinting; other studies presented these variables relative to time (MSR = 15 ± 7 m × min −1 ; HSR = 4 ± 1 m × min −1 ; sprinting = 3 ± 2 m × min −1 ) [ 30 , 33 , 37 , 47 , 49 , 55 , 58 , 66 , 68 70 ]. Regarding the number of sprints, the players did a mean of 30 ± 19 sprint actions per match [ 34 , 45 , 53 , 54 , 58 , 61 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female players covered a total distance of 9556 ± 795 m and 103 ± 6 m × min −1 during matches [ 30 41 , 43 , 45 , 48 63 , 65 70 ]. Considering zones of intensity, women soccer players performed 1429 ± 702 m in MSR, 830 ± 1414 m in HSR and 267 ± 275 m in sprinting; other studies presented these variables relative to time (MSR = 15 ± 7 m × min −1 ; HSR = 4 ± 1 m × min −1 ; sprinting = 3 ± 2 m × min −1 ) [ 30 , 33 , 37 , 47 , 49 , 55 , 58 , 66 , 68 70 ]. Regarding the number of sprints, the players did a mean of 30 ± 19 sprint actions per match [ 34 , 45 , 53 , 54 , 58 , 61 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, studies [ 32 35 , 41 , 43 , 46 , 48 , 54 , 56 , 63 , 65 , 67 , 69 , 70 ] reported that female players completed a total of 165 ± 129 ACC and 146 ± 141 DEC actions during the match. These actions were also presented in frequency per minute [ 30 , 43 , 48 , 49 , 54 , 57 , 66 , 68 ], distance travelled [ 31 , 36 ] and duration [ 38 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the lack of a signi cant correlation between the DF-ROM level of elite female soccer players and the quality of landing during SSJL can be attributed to various factors. Elite athletes have a lower injury rate than amateur athletes [30], exhibit better attention and decision-making processes [31], and achieve higher sports performance outcomes [11]. This may explain the statistically non-signi cant results for elite soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between DF-ROM and SSJL has been evaluated in male soccer players [9], the relationship between DF-ROM levels and soccer-speci c landing quality in female soccer players has not been investigated. Moreover, considering the physical performance differences between elite and amateur female athletes [11], the level of relationship between DF-ROM and SSJL may also vary depending on the athlete pro les. On the other hand, evaluating the current subject area with traditional correlation tests may hinder interpreting the relationship between DF-ROM and SSJL in elite and amateur female soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, no se coincide tal como se indica en las comparaciones con los valores referenciales de estudios en competiciones de máximo nivel internacional reportados por Bradley y Scott (2020). Las distancias totales, luego de un procesamiento, demuestran menores valores comparados con los resultados obtenidos sobre las diferencias o no de equipos u17 y u20 de competiciones brasileñas (Kobal et al, 2022), donde se hace una caracterización de equipos profesionales. Igual sucede cuando se contrasta con los datos aportados por Choice et al (2022), sobre jugadores participantes en la liga profesional, primera y tercera división.…”
Section: Discussionunclassified